2014
DOI: 10.15386/cjmed-275
|View full text |Cite
|
Sign up to set email alerts
|

Elastic stable intramedullary nailing for fractures in children – specific applications

Abstract: Elastic stable intramedullary nailing (ESIN) is a new minimally invasive technique for the treatment of pediatric fractures. It approximates the physiological healing process of bone, without opening the fracture site. Also, the operative stress is minimal because of the minimally invasive nature of the procedure, and the volume of implants is small, offering a very good stability without plaster cast immobilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 16 publications
0
10
0
1
Order By: Relevance
“…There has been an increasing trend towards operative management of long-bone shaft fractures 7,70 in recent decades. Diaphyseal fractures are characterized by limited potential for remodeling and spontaneous correction because of the distance from the physis 17 , which may justify more aggressive surgical treatment. There are also changes is patients' requests, economic circumstances, living habits and sports, which may have contributed to a change against surgical fixation 17 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been an increasing trend towards operative management of long-bone shaft fractures 7,70 in recent decades. Diaphyseal fractures are characterized by limited potential for remodeling and spontaneous correction because of the distance from the physis 17 , which may justify more aggressive surgical treatment. There are also changes is patients' requests, economic circumstances, living habits and sports, which may have contributed to a change against surgical fixation 17 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…At present, elastic stable intramedullary nailing (ESIN) is the gold-standard method of surgical treatment of forearm shaft fractures [13][14][15][16] . Compared with open reduction and plate fixation, ESIN is less traumatic and results in better cosmesis 17,18 . It shows an equally good union rate and is also feasible when open reduction is needed 1,19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32][33][34][35] In two studies, 36,37 distal tibia fractures were no distinguishable from diaphyseal fractures, and two studies 38,39 reported only the incidence of compartment syndrome. Three additional studies reporting only epidemiological data, 40 surgical technique, 41 and long-term outcomes, 42 respectively, were excluded.…”
Section: Resultsmentioning
confidence: 99%
“…The use of elastic stable intramedullary nails has almost become a routine treatment method for pediatric diaphyseal fractures of long bones in the last few years. There is much evidence that proves this method has the benefits of early immediate stability to the involved bone segment, which permits early mobilization and return to normal activities of the patients without immobilization, with very low complication rates [ 13 , 14 , 15 , 16 ]. The benefits of ESIN, compared to other surgical techniques, include shorter surgical time, minimal soft-tissue dissection, improved cosmesis, less pain, early mobilization, and relatively easy implant removal [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is much evidence that proves this method has the benefits of early immediate stability to the involved bone segment, which permits early mobilization and return to normal activities of the patients without immobilization, with very low complication rates [ 13 , 14 , 15 , 16 ]. The benefits of ESIN, compared to other surgical techniques, include shorter surgical time, minimal soft-tissue dissection, improved cosmesis, less pain, early mobilization, and relatively easy implant removal [ 13 , 14 , 15 , 16 ]. Although many authors recommend immobilization in the postoperative period, our previous study clearly showed that immobilization is not necessary and that there is no increased number of complications if immobilization did not occur [ 13 , 15 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%